Sub-Tenon Sustained Controllable Delivery of Dexamethasone for Treating Severe Acute Experimental Uveitis. (17th August 2020) - Zhao, Libei; Huang, Xuetao; Peng, Manqiang; Tan, Qian; Lin, Wenxiang; Khan, Muhammad Ahmad; Tang, Qiongyan; Lin, Ding
ABSTRACT: Purpose: To evaluate the efficacy of dexamethasone (DXM) through sub-tenon sustained controllable drug delivery system (SSCDDS) for treating severe acute experimental uveitis. Methods: Rabbits were treated with either DXM (treated group) or normal saline (control group) through SSCDDS. Clinical signs of uveitis were assessed at days 1, 3, 5, 7, and 14 after treatment. Histopathologic examinations were performed to evaluate inflammatory cell infiltration on posttreatment days 7 and 14. Results: All signs of experimental uveitis were reduced by SSCDDS of DXM according to clinical criteria, and the treated group had significantly less inflammation than the control group ( p <0.05). Histopathologic examinations showed severe inflammation and marked inflammatory cell infiltration in the control group, but minimal inflammation in the treated group. Conclusions: Sub-tenon sustained controllable delivery of DXM effectively suppresses severe acute inflammation in a rabbit model of uveitis. The proposed minimal invasive system might be a promising candidate for managing severe ocular diseases.